SOSIALISASI PENINGKATAN PEMAHAMAN MENGENAI CLIMATE CHANGE MELALUI SHARING SESSIONS DI KALANGAN REMAJA DALAM PEMBAHASAN KASUS KEBAKARAN HUTAN DI RIAU - Khoirunnisa Khoirunnisa (Universitas 17 Agustus 1945 Jakarta, 2023)
Nowadays, security issues have increased rapidly, not only regarding traditional security in the context of territorial security and military power of a country, but have expanded to non-traditional security issues. One example of a non-traditional security issue is the threat of haze pollution. Students as human beings with high intellectual and social control It is expected to contribute to society. This means that in this case, the role of students as social controllers is very important, and they are expected to contribute to the wider community in various aspects. Therefore, to realize this, the International Relations Student Association of the University of August 17, 1945, Jakarta took the initiative to hold community service activities by conducting socialization with students of SMAN 110 Jakarta through Sharing Sessions on Climate Change. This service activity is aimed at students of SMAN 110 Jakarta and aims to increase knowledge about climate change, especially the effects of forest fires, through case studies of forest fires that occurred in Riau and make it happen in everyday life.